Originally Posted by

**TomCat** Okay. Here it goes. I am wondering if I am doing the following correctly.

1) f(x) = 3x-2/-5x+7; g(x) = 7x-3/5x+6

Find f of g.

So I start by subbing them in so I get:

(3(7x-3/5x+6) -2) / (-5(7x-3/5x+6) + 7

I then multiply the 3 and -5 into the fractions:

((21x-9/5x+6)-2) / ((-35x+15/5x+6)+7)

Then I get a common denominator for the -2 and the 7:

((21x-9/5x+6) - (10x+12/5x+6)) / ((-35x+15/5x+6) + (35x+55/5x+6))

Then I subtract, add, and simplify to get:

11x-21/70

____________________

2) Find the inverse of f(x) = (3x-2/-5x+7)+5

I start by swapping the x's and y's:

x = (3y-2/-5y+7)+5

Then I multiply both sides to get:

-5xy+7x = (3y -2) +5